Suggested framework for design effort and acceptance criteria for underground mine excavations - Dunn, MJ; de Graaf, PHJ (Ground Support 2023: 10th International Conference on Ground Support in Mining, 2023)
It is generally accepted that a higher confidence and reliability is required for the design of underground mining excavations as it passes through the various study stages (conceptual, pre-feasibility, feasibility) and the implementation and operational phases. Often this is related to the amount and type of geotechnical data available to support the underground excavation design; however, many additional factors need to be considered. Many of these factors are interrelated and cannot be chosen or dealt with in isolation. This requires consideration of context, intent, consequences, uncertainty, and risk. The design effort for underground mine excavations needs to consider the following: Excavation design lifetime, use and criticality to continuing mining operations. Excavation hazard and risk (principally safety and economic, but also reputational and licence to operate). Anticipated failure mechanisms (scale, frequency, and predictability). Data availability (confidence, spatial distribution, representativeness, type, quantity, and quality). Appropriate design methods (related to risk profile and failure mechanisms). Design criteria which consider the excavation use and serviceability requirements. Only by understanding the risks associated with the excavation and its intended use, is it possible to determine the design effort and appropriate design criteria. The paper will discuss the aspects outlined above and propose a scheme that relates the design effort to the excavation risk. This approach has been useful for providing a framework, for alignment of consultants and internal stakeholders in prioritising design study and investigation area focus, and commensurate rigour in approach for recent projects.
Keywords: design; acceptance criteria; uncertainty; risk